Crisis management in tourism: preparing for recovery - Pforr, Christof; Hosie, Peter (The Haworth Press, 2007)
Anticipating and preparing to deal with the threat of crises precipitated by disaster from natural and people-made catastrophes is an important challenge facing tourism. As an industry tourism is particularly susceptible to such negative events putting the sector under almost constant threat of a crisis. Before the catastrophes of 9/11 and the Asian Tsunami of 2004 crisis management in tourism was essentially a reactive response, as opposed to a state of proactive anticipation. A review of the emerging literature on crisis management in tourism is given to identify the foci of the current academic discourse. More systematic input by human resource management was identified as a way to assist tourism businesses in preparing for and dealing with crises. By discussing crisis management within a services management context, a contribution is made to the debate on the need for proactive crisis management within the tourism industry. A central plank to this position is that the preparation stage of crisis management in tourism is the actual beginning of any strategic response to recovery. Well conceived and executed human development is promoted as an initiative and key component of crisis preparation and management. Developing the potential of human capital at the industry and enterprise level to deal with crisis management is a way of reducing the vulnerability of tourism enterprises to crises. Measures are suggested that may be taken to prepare tourism businesses for crisis situations.